Political Discourses at the Extremes - Sullet-Nylander , Françoise; Bernal, Maria; Premat, Christophe; Roitman, Malin (2019)
"The authors of this edited volume focus on the emergence of populist discourses, coming from movements or parties from Romance-speaking countries in Europe and in Latin America. By combining linguistics, social and political sciences in a discourse analytical approach, the sixteen papers enlighten the mechanisms behind populist discourses yielding from different socio-cultural and political contexts. The common denominator of the studies is the focus on the discursive and rhetorical characteristics of recently emerged movements of populism in both continents. Investigating expressions of these political movements is highly relevant in today’s society, where the growing number of populist discourses has become a pre-eminent issue, alongside people’s increasing insecurity regarding future political and environmental challenges. The primary audience of this volume are researchers working in the fields of political discourse analysis; however, this book may benefit anybody with interest in language in politics. ******* ‘This volume will be a valuable contribution to the study of populist discourse at the political extremes. It hardly needs to be mentioned that this is one of the most topical issues in political discourse throughout the world today. The specifics of populist discourse are often misunderstood, so I have found this volume enlightening and helpful to increasing my own understanding.’ — Rodney Williamson, University of Ottawa ‘The anthology provides indeed a fine analysis of discourses connected to different socio-cultural and political contexts […] Since it brings together researchers specialized in media and political discourse analysis, it contributes to a large extent to promote a deeper understanding of current political discourses and extremist ideologies.’ — Ana Pano Alamán, University of Bologna"